2019
DOI: 10.21203/rs.2.17327/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paroxetine suppresses reactive microglia-mediated but not lipopolysaccharide-induced inflammatory responses in primary astrocytes

Abstract: Background: Astrocytes are the most abundant glial cells in a brain that mediate inflammatory responses and provide trophic support for neurons. We have previously disclosed that paroxetine, a common selective serotonin reuptake inhibitor, ameliorates LPS-induced microglia activation. However, it remains elusive of the role of paroxetine in astrocytic responses. Methods: Isolated primary astrocytes were pretreated with paroxetine and stimulated with different stimuli, lipopolysaccharide (LPS) or microglia cond… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Some authors have reported a robust response of astrocytes to LPS/IFNγ (e.g. Hamby et al, 2010; Hua et al, 2002), whereas others report no response (Possel et al, 2000; Sheng et al, 2011; Zhang et al, 2020), as observed here. The reasons for these differences are not clear but could stem from contaminating microglia in putatively pure astrocyte cultures or to differing culture conditions.…”
Section: Discussionsupporting
confidence: 69%
“…Some authors have reported a robust response of astrocytes to LPS/IFNγ (e.g. Hamby et al, 2010; Hua et al, 2002), whereas others report no response (Possel et al, 2000; Sheng et al, 2011; Zhang et al, 2020), as observed here. The reasons for these differences are not clear but could stem from contaminating microglia in putatively pure astrocyte cultures or to differing culture conditions.…”
Section: Discussionsupporting
confidence: 69%
“…As a comparison, in a recent study where primary astrocytes were cultured with serum-containing medium, paroxetine was shown to suppress microglia conditioned medium-stimulated astrocytic in ammation partially via the p65/NFκB pathway, but not by STAT3 and JNK1/2. In addition, paroxetine showed no impact on lipopolysaccharide-induced astrocytic responses [18]. These results indicate that the phenotype (A1, A2, resting, or mixed) and the stimulus matter how antidepressants play a role in astrocytes.…”
Section: Discussionmentioning
confidence: 78%
“…Inhibitors SP600125 (S1876) and AG490 (HY-12000) were respectively purchased from Beyotime (Shanghai, China) and MedChemExpress (Monmouth Junction, NJ, USA). Immuno uorescence As previously described [18], cells were xed in 4% paraformaldehyde for 30 min and washed with phosphate buffered saline (PBS), followed by permeabilization in 0.2% Triton X-100 for 20 min. Samples were blocked with 5% bovine serum albumin (ST023; Beyotime, Shanghai, China) for 1 h and then incubated with primary antibodies against GFAP (MAB360; Merck Millipore, Billerica, MA, USA), p65 (8242; Cell Signaling, Boston, MA, USA), C3 (EPR9394; Abcam, Cambridge, United Kingdom) or S100A10 (11250-1-AP; Proteintech, Rosemont, IL, USA) at 4 °C overnight.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…Otud1 (OTU Deubiquitinase 1) is a deubiquitinating enzyme that can regulate the content of IFN regulatory factor 3 in mice after LPS stimulation. 34 Manf (mesencephalic astrocyte–derived neurotrophic factor), an anti-inflammatory factor, 35 reduces LPS-induced IL-1β, TNF-α, and Interferon γ proinflammatory cytokines by regulating the phosphorylation of NF-κB and p38 MAPK pathways. 36 In addition, it has been shown to be a potential target gene for the treatment of acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%